(untitled) (Studia austriaca, 2024)
Silence is commonly understood as a void – in this sense, there is no silence. The figure of thought – silence, calibrates meaning within relationships. I argue that the meaning of several writings in Franz Schubert’s diary has a much larger impact than is commonly understood to this day. Specific tones and ‘beep’ sequences evoke emotions and a deep layer of melancholy, all of which serve as the guiding force in Schubert’s music. In contrast, silence – the moment in which meaning becomes elusive – impoverishes that moment within the lines of the diary note Mein Traum.